School Starting Age and the Crime‐age Profile. (8th August 2016) - Landersø, Rasmus; Nielsen, Helena Skyt; Simonsen, Marianne
Abstract : This article uses register‐based data to investigate the effects of school starting age on crime. Through this, we provide insights into the determinants of crime‐age profiles. We exploit that Danish children typically start first grade in the calendar year they turn seven, which gives rise to a discontinuity in school starting age for children born around new year. Our analysis speaks against a simple invariant crime‐age profile as is popular in criminology: we find that higher school starting age lowers the propensity to commit crime at young ages. We also find effects on the number of crimes committed for boys.